2012
DOI: 10.1016/j.str.2012.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Out but Not In: The Large Transmembrane β-Barrel Protein FhuA Unfolds but Cannot Refold via β-Hairpins

Abstract: How transmembrane β-barrel proteins insert and fold into membranes and by which factors they destabilize, unfold, and misfold represents a field of intense studies. Here, we use single-molecule force spectroscopy to characterize the un- and refolding of the ferric hydroxamate uptake receptor (FhuA), which is one of the largest β-barrel proteins of the outer membrane of Escherichia coli. Applied to mechanical stress, FhuA undergoes a complex unfolding pathway in which each of the 11 β-hairpins unfolds one after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 33 publications
(62 reference statements)
5
62
0
Order By: Relevance
“…Furthermore, because these interactions alter the physical properties of LacY (reviewed in ref. 9), the energetic, kinetic, and mechanical properties of LacY that fulfill different functional roles during transport remain to be characterized.Atomic force microscopy (AFM)-based single-molecule force spectroscopy (SMFS) has been applied to localize and quantify interactions that stabilize structural elements of an increasing number of native membrane proteins (20)(21)(22)(23)(24)(25). Because SMFS can be used with membrane proteins embedded in native or synthetic lipid membranes under physiological conditions, the method has been used to assess interactions that change upon substrate binding, insertion of mutations, and assembly or lipid composition of the membrane (26-35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, because these interactions alter the physical properties of LacY (reviewed in ref. 9), the energetic, kinetic, and mechanical properties of LacY that fulfill different functional roles during transport remain to be characterized.Atomic force microscopy (AFM)-based single-molecule force spectroscopy (SMFS) has been applied to localize and quantify interactions that stabilize structural elements of an increasing number of native membrane proteins (20)(21)(22)(23)(24)(25). Because SMFS can be used with membrane proteins embedded in native or synthetic lipid membranes under physiological conditions, the method has been used to assess interactions that change upon substrate binding, insertion of mutations, and assembly or lipid composition of the membrane (26-35).…”
mentioning
confidence: 99%
“…Atomic force microscopy (AFM)-based single-molecule force spectroscopy (SMFS) has been applied to localize and quantify interactions that stabilize structural elements of an increasing number of native membrane proteins (20)(21)(22)(23)(24)(25). Because SMFS can be used with membrane proteins embedded in native or synthetic lipid membranes under physiological conditions, the method has been used to assess interactions that change upon substrate binding, insertion of mutations, and assembly or lipid composition of the membrane (26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…While the refolding pathway of chemically denatured OmpA protein appears to be best described by the concerted process, it is interesting to note that mechanical unfolding of the related protein KpOmpA from Klebsiella pneumoniae results in a stepwise unfolding process where individual β hairpins unfold successively [64]. Similar behavior has also been observed in β barrels OmpG and FhuA [65,66]. Moreover, in the case of OmpG, refolding was also observed and occurred in a stepwise fashion involving insertion of individual β hairpins [65].…”
Section: Folding Pathways For β Barrelsmentioning
confidence: 76%
“…In 2009, Sapra et al [59] investigated the unfolding of the membrane protein OmpG that was reconstituted in lipids and revealed that the unfolding pathway was via amino acids 8,43,83,126,166,204, and 248. In 2012, Thoma et al [65] investigated the unfolding of membrane protein FhuA: after attaching the E. coli polar lipid bilayers containing reconstituted FhuA molecules onto freshly cleaved mica, AFM imaging was first performed to acquire the morphology of FhuA (Fig. 3f, g), and then SMFS was performed to mechanically unfold single FhuA molecules, showing that the unfolding pathway of FhuA was amino acid 92, 161,192,229,297,367,447,492,536,584,634,681 (Fig.…”
Section: Mechanically Unfolding Membrane Proteins With Smfsmentioning
confidence: 99%